Pengaruh Kompetensi Spiritual Guru Pendidikan Agama Kristen Terhadap Pertumbuhan Iman Siswa - Evi Nuriyani Simatupang (IAKN Tarutung, 2020)
This research aims to find out the influence of Christian Religion Education teacher’s spiritual competence on the students’ faith growth of grade V SD Negeri No. 175758 Hutagurgur, with the hypothesis there is a positive and significant effect of Christian Religion Education teacher’s spiritual competence on the students’ faith growth of grade V SD Negeri No. 175758 Hutagurgur, Sipahutar Subdistrict, Academic Year 2019/2020. The research population is 30 students, and all of those are the research sample as well. Data were collected with a closed questionnaire of 30 items compiled by the author based on variable indicators by the experts’ theories. The instrument had been previously tested to 30 students who were not the research respondents, hence the instruments’ validity and reliability had been tested. The results of data analysis shows that there is a positive and significant effect of Christian Religion Education teacher’s spiritual competence on the students’ faith growth of grade V SD Negeri No. 175758 Hutagurgur, Sipahutar Subdistrict, Academic Year 2019/2020, with the determination coefficient (r2) = 35,57%, and the significance test obtains Fcount Ftable = 16,55 4,20 . Thus, it can be concluded that H0 is rejected and Ha is accepted.